2015
DOI: 10.4103/1596-3519.148737
|View full text |Cite
|
Sign up to set email alerts
|

Depression among adolescents attending secondary schools in South East Nigeria

Abstract: Adolescents exhibit different levels of depression with a female preponderance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…[21,3942] A cross-sectional survey indicated that 23% of Nigerian students were depressed. [43] Similarly, Chinawa et al [2] surveyed the prevalence of depression in Southeastern Nigerian States and found that students were experiencing depression. Despite this, little research is available regarding the role of cognitive-behavioral intervention in improving anxiety and depression symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[21,3942] A cross-sectional survey indicated that 23% of Nigerian students were depressed. [43] Similarly, Chinawa et al [2] surveyed the prevalence of depression in Southeastern Nigerian States and found that students were experiencing depression. Despite this, little research is available regarding the role of cognitive-behavioral intervention in improving anxiety and depression symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Female adolescent were found to manifest higher mean score in severity of depression than male participants. This finding is supported by Kumar and Akoijam [23], Jha, Singh and Aggrawal [22], Borchard, [34] and Chinawa, et al [19]. Depression is about twice as common in women as in men, with about 1 in 4 women suffering from depression at some point during her lifetime.…”
Section: Discussionmentioning
confidence: 51%
“…This finding is in agreement with previous studies. For instance in a prevalence study of depression among Nigerian children, Chinawa, Manyike, Obu, Aronu, Odutoa and Chinawa [19] reported a 7.4% rate of severe depression among 12 years old Nigerian children; Umeh [20] returned a 32.1% prevalence rate while Okwaraji, Aguwa, Onyebueke Shiweobi-Eze [21] reported that 20.0% and 4.5% of the undergraduates were found to be mildly and moderately depressed respectively. Among Indian adolescents the prevalence of depression was found to be 49.2% out of which 7.7% were severe depression [22].…”
Section: Discussionmentioning
confidence: 99%
“…The study further reported that Female gender is a risk factor for depression and that Children whose parents are separated showed higher incidences of depression in all the spectra studied [20] . In their study on depression among rural adolescents, Black, Roberts and Li-Leng [21] reported that 18% of the rural adolescents studied screened positive for depression, 41% reported low mood much of the time while 20% experienced occasional or more frequent self-harm or suicidal thoughts, plans or actions.…”
Section: Introductionmentioning
confidence: 64%